2010
DOI: 10.1007/s10258-010-0056-6
|View full text |Cite
|
Sign up to set email alerts
|

Contagion effects of the subprime crisis in the European NYSE Euronext markets

Abstract: This paper presents three tests of contagion of the US subprime crisis to the European markets of the NYSE-Euronext group. Copula models are used to analyse dependence structures between the US's and the other markets in the sample, in the pre-crisis and in the subprime crisis periods. The first test assesses the existence of contagion on the relevant markets' indices, the second checks the homogeneity of contagion intensities, and the third compares contagion in financial and in industrial sectors' indices. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 31 publications
(25 reference statements)
0
57
0
7
Order By: Relevance
“…Moreover, it allows returns to have asymmetric and heavy tail distributions, which some empirical evidence has shown to be adequate in describing financial returns. Horta et al (2010) concluded for a smaller data-set that there was contagion of the US subprime crisis in the European stock markets belonging to the NYSE Euronext group. We have now confirmed that result and have added that the portfolio-rebalancing channel is a vital crisis transmission mechanism and that the flight-to-quality phenomenon is present in all analyzed stock markets.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, it allows returns to have asymmetric and heavy tail distributions, which some empirical evidence has shown to be adequate in describing financial returns. Horta et al (2010) concluded for a smaller data-set that there was contagion of the US subprime crisis in the European stock markets belonging to the NYSE Euronext group. We have now confirmed that result and have added that the portfolio-rebalancing channel is a vital crisis transmission mechanism and that the flight-to-quality phenomenon is present in all analyzed stock markets.…”
Section: Introductionmentioning
confidence: 98%
“…The subprime crisis, for example, was not actually confined to the US mortgage markets. As a result of securitization, the crisis spread to the entire financial market, not only in the US, but also to all developed countries (Horta et al, 2008). Within a couple of months, the Dow Jones index plummeted from 14,093 (September 28, 2007) to 12,980 (November 23, 2007) and then to 6,626 (March 6, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…One alternative method resides in using parametric marginal distribution functions instead. Two alternative parametric functions commonly used to fit the returns of financial assets are the Gaussian and Student's t marginal distributions (Horta et al, 2010). We estimate the copula functions using these parametric marginal distributions.…”
Section: Methodology and Empirical Resultsmentioning
confidence: 99%